2022
DOI: 10.1007/jhep01(2022)167
|View full text |Cite
|
Sign up to set email alerts
|

Initial value problem in string-inspired nonlocal field theory

Abstract: We consider a nonlocal scalar field theory inspired by the tachyon action in open string field theory. The Lorentz-covariant action is characterized by a parameter ξ2 that quantifies the amount of nonlocality. Restricting to purely time-dependent configurations, we show that a field redefinition perturbative in ξ2 reduces the action to a local two-derivative theory with a ξ2-dependent potential. This picture is supported by evidence that the redefinition maps the wildly oscillating rolling tachyon solutions of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 64 publications
2
19
0
Order By: Relevance
“…We have presented explicit results for a representative HES at mass level N = 100, but the same systematics holds for different mass levels. From the point of view of the analysis of the chaotic information present in HES interactions, one can quantitatively improve the measure of chaos with additional parametrization of the information content based on modern techniques of quantum information theory [45]- [50] In section 2 we have analyzed how the thermal nature of the decay amplitude is intimately related to its chaotic nature, in particular we have observed that the chaotic analytical structure, which appear as a non trivial dressing factor, originates a Boltzmann factor which encodes the thermal information of the decay process. Exploiting the exact analytical result of the decay process of a generic HES that decays into a less excited, yet generic HES, through the emission of scalar particle, such as the tachyon, we have computed the energy spectrum of HES.…”
Section: Jhep04(2023)052 4 Conclusion and Future Directionsmentioning
confidence: 99%
“…We have presented explicit results for a representative HES at mass level N = 100, but the same systematics holds for different mass levels. From the point of view of the analysis of the chaotic information present in HES interactions, one can quantitatively improve the measure of chaos with additional parametrization of the information content based on modern techniques of quantum information theory [45]- [50] In section 2 we have analyzed how the thermal nature of the decay amplitude is intimately related to its chaotic nature, in particular we have observed that the chaotic analytical structure, which appear as a non trivial dressing factor, originates a Boltzmann factor which encodes the thermal information of the decay process. Exploiting the exact analytical result of the decay process of a generic HES that decays into a less excited, yet generic HES, through the emission of scalar particle, such as the tachyon, we have computed the energy spectrum of HES.…”
Section: Jhep04(2023)052 4 Conclusion and Future Directionsmentioning
confidence: 99%
“…(2.5) turns out to be finite in the high-energy regime [29][30][31][32]. Very interestingly for such nonlocal theories, despite the presence of infiniteorder time derivatives, a consistent initial value problem can be formulated in terms of a finite number of initial conditions [33][34][35].…”
Section: Jhep11(2022)104mentioning
confidence: 99%
“…202300255 In recent years, an increasing number of String Theory, and Particle Physics, problems have been addressed with optimization algorithms and machine learning, see e.g., refs. [8][9][10][11][12][13][14][15]. In this work we present an algorithm, based on evolutionary algorithms (EAs) and Bayesian optimization, to construct smooth horizonless supergravity solutions.…”
Section: Introductionmentioning
confidence: 99%